IMPLIED AUTHORIZATION? VIOLATION OF BANK SECRECY IN CONSUMER PROTECTION PROCEDURES THAT DEAL WITH PASSIVE OPERATIONS - Huamán Núñez, Ayrton Erick (2024)
Over the past few years, some Indecopi decision-making bodies specialized in consumer protection have requested information from various financial entities about the passive operations of complaining consumers, within the framework of a sanctioning administrative procedure. This requirement is legally invalid, as it violates the pro hominem constitutional principle, the material truth principle and the consent principle in matters of personal data. However, if the financial entity provides said information in the context indicated above, it could not be penalized, since one of the exemptions from liability provided in the General Administrative Procedure Law would be configured.